Lifestyle Description in Kidney Failure Patients Pre Hemodialysis - Hutagalung, Perak M.A; Pasaribu, Ester; Silaban, Jojor (Universitas Prima Indonesia, 2024)
Chronic kidney failure is a situation where the kidney's performance slowly decreases so that it cannot maintain optimal body balance until the end and can cause a person to undergo hemodialysis. Chronic kidney disease can be triggered by various lifestyle factors, including consuming herbal medicines, drinks containing alcohol, smoking, not drinking enough water, and consuming energy supplement drinks. This research aims to find out what the lifestyle of pre-hemodialysis chronic kidney failure patients is like in the hemodialysis room at Sidikalang Regional Hospital. This research method is this type of research, namely quantitative descriptive research, carried out from January to April 2024, with a population of 42 respondents using total sampling techniques and data analysis using univariate analysis. The results of this research show that based on the consumption of water <2L/day as much as 64.3%, holding BAK as much as 78.6%, consuming salty foods as much as 85.7%, consuming medicines as much as 85.7%, consuming traditional medication as much as 59.5%, smoking >10 cigarettes/day as much as 59.5%, alcohol consumption as much as 35,7%, and exercising <3x/week as much as 85.7%. The suggestion in this research is that efforts are needed to improve lifestyle towards a healthy lifestyle to prevent the incidence of chronic kidney failure.